The challenge of upgrading white shrimp production in central Vietnam and the potential of farming cooperatives - Schwabe, Julian; Nguyen, Chung Van; Hassler, Markus (DIE ERDE – Journal of the Geographical Society of Berlin, 2021)
Aquaculture in Vietnam expanded significantly over the past two decades and contributed to poverty alleviation among smallholders. Upstream value chains of shrimp farming in Vietnam are characterized by a high degree of informality, a high number of intermediate layers in trade and power asymmetries between farmers, suppliers and buyers. Input supply such as feed and fingerlings for shrimps account for 60% to 80% of overall cost in white shrimp production. Reducing the cost of input supply would therefore significantly improve income and welfare of farmers. Hence, this study focuses on the characteristics of business relationships between farmers and input suppliers and explores the possibilities of farmers to improve their bargaining position. In particular, the potential of horizontal coordination in the form of cooperatives is evaluated. Characteristics of business relationships and possibilities to (individually and collectively) improve their bargaining positions of farmers are evaluated within the conceptual frame of global value chains and upgrading. The paper argues that despite previous unsuccessful attempts to establish cooperatives, horizontal coordination is an important measure in order to counter high dependencies from supply agents. However, in order to be successful, attempts to coordinate need a clear value proposition for farmers, engagement and communication among farmers and government support in funding the necessary infrastructure.